"Pottery" of Porous Graphene Materials. (30th March 2015) - Li, Yingru; Chen, Ji; Huang, Liang; Li, Chun; Shi, Gaoquan
<x xml:space="preserve">Abstract</x> Porous graphene "pottery" is prepared via a process imitating traditional pottery preparation technology. This method is simple, cheap, scalable, and eco‐friendly. The "pottery" of porous graphene materials has an ultrahigh mass density, a large SSA, good conductivity, and unique anisotropic electrical and mechanical properties, promising for the practical applications in supercapacitors.